Review On Ayurvedic Management Of Hypertension - Salunkhe, Shraddha Anandrao; Padwal, Komal Sudam; Shah, Sonal (International Research Journal of Ayurveda & Yoga, 2021)
Introduction From an Ayurvedic perspective, several ideas have been offered to explain hypertension, however there is no unanimity among experts. To close this gap, researchers are attempting to gain a deeper grasp of the applied physiology and etio-pathogenesis of hypertension using Ayurvedic concepts. A thorough examination of extant Ayurvedic literature was conducted in order to gain a better understanding of the physiology of blood pressure and the etio-pathogenesis of hypertension from an Ayurvedic perspective. Aims and objectives To assess and elaborate the etiological components of hypertension. Material and methods Ayurvedic text books and concert notes provided detailed information on pathology, aetiology, and management. To further develop the diagnosis and therapy of hypertension, national-international, index non-index, peer-reviewed articles were also explored. Results This hypertension review demonstrates that following Ayurvedic rules for medicine would effectively regulate blood pressure without causing any harmful side effects. Pathya and Apathyaas Aahar - Vihar (diet management and proper lifestyle) and Yoga are also mentioned in Ayurveda as ways to control hypertension. These help to keep the human body in a state of equilibrium, preventing hypertension. Conclusion Hypertension is a disease caused by a change in one’s lifestyle. Changes in our lifestyle and medications are used to treat it. Various antihypertensive allopathic medications are available in modern science for the management of blood pressure. These antihypertensive medications can help regulate blood pressure, but they will not treat high blood pressure permanently. When we stop taking medication, our blood pressure and other health issues will rise. As a result, for a healthy future, everyone must adhere to the Ayurvedic hypertension regimes.